2014
DOI: 10.1007/s10803-014-2216-5
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder (ASD) and Unlawful Behaviour: Where Do We Go from Here?

Abstract: There exists now a body of research that describes case studies of individuals with autism spectrum disorder (ASD) who have engaged, or are alleged to have engaged, in a range of illegal behaviours, and that attempts to estimate the prevalence of ASD at different stages of the criminal justice process. Taken together, this research does suggest that some individuals with ASD will come into contact with the criminal justice system, but many questions regarding this apparent association remain unanswered. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…For example, social naivety, reduced victim empathy, theory of mind deficits, and special interests/obsessions (Dein & Woodbury-Smith, 2010;Geluk et al, 2012;Howlin, 2004;Wing 1981a) have all been identified, along with weak central coherence, which has been suggested to impact upon an individual's ability to be able to foresee and understand the consequences of their actions (e.g. Woodbury-Smith & Dein, 2014;Murphy, 2010aMurphy, , 2010b. A number of these factors are congruent with existing theories of offending, such as General Strain Theory (Agnew, 1992(Agnew, , 2013, and more specifically, models of victim empathy deficits and cognitive distortions for sexual offending behaviours (e.g.…”
Section: Ascs and Offender Treatmentmentioning
confidence: 99%
“…For example, social naivety, reduced victim empathy, theory of mind deficits, and special interests/obsessions (Dein & Woodbury-Smith, 2010;Geluk et al, 2012;Howlin, 2004;Wing 1981a) have all been identified, along with weak central coherence, which has been suggested to impact upon an individual's ability to be able to foresee and understand the consequences of their actions (e.g. Woodbury-Smith & Dein, 2014;Murphy, 2010aMurphy, , 2010b. A number of these factors are congruent with existing theories of offending, such as General Strain Theory (Agnew, 1992(Agnew, , 2013, and more specifically, models of victim empathy deficits and cognitive distortions for sexual offending behaviours (e.g.…”
Section: Ascs and Offender Treatmentmentioning
confidence: 99%
“…There have also been recent attempts to formulate treatments within forensic psychiatric services which are specific to the needs of individuals with ASDs (Kelbrick and Radley, 2013;Langdon et al, 2013) given that generic programmes will not be as effective as more specialised interventions (Browning and Caulfield, 2011). However, these new formulated treatments need further evaluation using larger samples (Woodbury- Smith and Dein, 2014).…”
Section: Screening and Interventions For Offenders With Asdmentioning
confidence: 99%
“…Second, despite numerous studies exploring rates of recidivism after discharge from secure psychiatric care (Coid et al, 2007) and prisons (Langan and Levin, 2002), there appears to be limited research investigating the factors which impact positively and negatively on recidivism in offenders with ASD who finish their prison sentences, or individuals with ASD discharged from secure psychiatric care (Woodbury- Smith and Dein, 2014). Third, more research on the prevention of crime commission by individuals with ASDs as well as research exploring ways to reduce the risk of individuals with ASDs being at risk of victimisation is warranted.…”
Section: Future Directionsmentioning
confidence: 99%
“…These include diagnostic difficulties arising as a consequence of time constraints and difficulties in obtaining adequate developmental histories. Woodbury-Smith & Dein (2014) highlighted the need for research to be translated into clinical practice. They suggested that training to increase the ability of prison staff to recognise symptoms of ASD, the development of specific pathways of care for individuals with ASD in prison and the introduction of specialist wings for prisoners with ASD may help to improve their custodial experience.…”
Section: Management Of People With Autistic Spectrum Disorders In Primentioning
confidence: 99%